D DETERMINANTS OF PARENTS’ INTENTION TO VACCINATE THEIR CHIL-DREN AGED 12–17 YEARS AGAINST COVID-19 IN NORTH KIVU (DRC) - bateyi-mustafa, stephane-hans; Kabamba , Michel; Baswayi , Clément Bula; Onyango.O, Rosebella (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
Background: Vaccinating children against COVID-19 is an essential public health strategy in order to reach herd immunity and prevent illness among children and adults. Parents are facing tremendous stress in relation to the COVID-19 pandemic and the effectiveness of the COVID-19 vaccination program for children. In this study, we aimed to investigate parents’ willingness to vaccinate their children against COVID-19 in North Kivu province (DRC). Methods: A cross-sectional survey between 1 December 2021 to 20 January 2022 in six health zones (Goma, Karisimbi, Butembo, Beni, Kamango, and Katwa) was conducted in the province of North Kivu. In each health zone, we selected five clusters (Health area) using the method of probabilistic selection proportional to population size. In total, 522 parents participated in our study. Results: Overall, 32.8% of parents intended to vaccinate their children. In the multivariate analysis, a younger age of parents (aOR: 2.40, CI: [1.50–3.83]), a higher level of fear that “a member of my family” could contract COVID-19 (aOR: 2.35, CI: [1.38–4.02]), a higher level of perceived vulnerability to COVID-19 within the family (aOR: 1.70, CI: [1.005–2.2881]), a higher level of perceived susceptibility to COVID-19 within the family (aOR: 3.07, CI: [1.80–5.23]), and a history of vaccination against COVID-19 among parents (aOR: 16.47, CI: [8.39–32.33]), were all significantly associated with the intention of parents to have their children or adolescents vaccinated. Conclusion: The willingness of parents to vaccinate their children against COVID-19 was low in North Kivu. In this region there is an undeniable need to reassure the population about vaccine safety for both children and adults. Public health authorities should also address widespread misinformation about vaccines in a timely manner.